Kontribusi Pencitraan (Akreditasi, Kualitas Pelayanan Dan Promosi ) Terhadap Minat Kuliah Di Universitas Slamet Riyadi Surakarta - Dewi, Ira Hety Anggar; , Prof. Dr. Sutama, M.Pd (2016)
The purpose of this research was to test the contribution of accreditation, quality of service and promotion against the interest of college freshmen at the University of Slamet Riyadi. Approach this research usingquantitative methods. The population of 1200 students and a sample of 300 students. The technique of data collection with the questionnaire. Technique of data analysis with multiple linear regression analysis, classic assumption test previously done: heteroskedastisitas, multicollinearity, normality and autocorrelation. Research results: 1) accreditation, quality of service and promotions simultaneously contribute significantly to interest the lectures (p = 0.000) amounted to 11.6%. 2) partially Accreditation does not contribute significantly to interest the lectures (p = 0.666) contribution is effective (SE) of 0.28% 3) quality of service partially contribute significantly to interest the lectures (p = 0.000) effective contribution (SE) of 4% 7.99) Promotion partially contribute significantly to interest the lectures (p = 0.020) effective contribution (SE) amounted to 3.33%.